A kind of heat-resistant ceramic material and preparation method thereof
By forming a composite oxide coating on the surface of the modified silicon carbide fibers and reacting with boron carbide powder to form metal boride, the corrosion and insufficient performance of silicon carbide ceramic materials in high-temperature water-oxygen environment is solved, and the high-temperature toughness and mechanical properties of the material are significantly improved.
Patent Information
- Application Number
- CN202411689743.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The prior art is difficult to effectively prevent the corrosion of water vapor on silicon carbide ceramic materials in high temperature environments, and the oxidation resistance and mechanical properties of the materials are insufficient.
By forming a composite oxide coating on the surface of the modified silicon carbide fibers and reacting with boron carbide powder at high temperatures to generate metal borides, the water oxygen resistance and mechanical properties of the material are improved.
The high-temperature toughness, mechanical properties and water-oxygen corrosion resistance of ceramic materials have been significantly improved, and the lack of performance of materials in the prior art under high-temperature water-oxygen environment is solved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a temperature-resistant ceramic material and a preparation method thereof. Background Art
[0002] The engine is the core component of various aviation and aerospace vehicles. Increasing the combustion chamber temperature of the engine, for example, to above 2200°C, requires higher requirements for the materials of the engine combustion chamber, and requires a certain degree of protection against the water vapor generated by the combustion of high calorific value fuels. Silicon carbide ceramic-based composite materials have the advantages of high temperature resistance, oxidation resistance, light weight and high strength. They have a higher temperature resistance limit than nickel-based alloys and are widely used in aviation engines, solid fuel engines, conventional liquid engines, etc.
[0003] Under high temperature conditions, dense SiO2 will form on the surface of silicon carbide. 2 However, if there is water vapor, the layer will become porous due to the corrosion of water vapor, thereby losing its protective ability and accelerating corrosion. In the prior art, the surface of silicon carbide is often coated with oxide to prevent the erosion of water vapor, such as B 2 O3、SiO 2 、ZrO 2 Oxides such as ferrites can delay the corrosion of water vapor at high temperatures. However, due to the limitation of the material's own temperature resistance, it is difficult to increase the high-temperature water oxidation resistance to a higher level. Summary of the invention
[0004] The invention discloses a heat-resistant ceramic material and a preparation method thereof. The heat-resistant ceramic material comprises modified silicon carbide fiber, boron carbide powder, zirconium oxide powder, yttrium oxide powder, tantalum pentoxide powder and titanium boride powder in proportion by mass. The average particle size of the boron carbide powder is larger than the diameter of the silicon carbide fiber, and the average particle size of the zirconium oxide powder, yttrium oxide powder and tantalum pentoxide powder is smaller than the diameter of the silicon carbide fiber. The invention controls the oxide composition, the temperature and time of low-temperature sintering and high-temperature sintering, reacts on the surface of the modified silicon carbide fiber to generate a composite oxide coating layer, and reacts part of the oxide on the surface of the coating layer with the boron carbide powder at high temperature to generate a metal boride with higher hardness and oxidation resistance. The oxide coating layer improves the water and oxygen resistance and toughness of silicon carbide, and the metal boride improves the mechanical properties and high-temperature water and oxygen corrosion resistance of the ceramic material.
[0005] Specifically, the present invention discloses a method for preparing a temperature-resistant ceramic material, the method comprising:
[0006] 1) Placing the SiC fiber in an atmosphere furnace and heating it in an oxidizing atmosphere to oxidize the surface of the SiC fiber to obtain modified SiC fiber;
[0007] 2) Weigh the modified SiC fiber, B 4 C powder, ZrO 2 Pink, Y 2 O 3 Pink, Ta 2 O 5 Powder and HfO 2 The powder is mixed evenly; wherein the average particle size of the B4C powder is larger than the diameter of the SiC fiber, and the ZrO 2 Pink, Y 2 O 3 Pink, Ta 2 O 5 The average particle size of the powder is smaller than the diameter of the SiC fiber;
[0008] 3) placing the mixture in a hot pressing sintering furnace at a pressure of 20-30 MPa, heating to 1450-1550°C under argon protection, and hot pressing sintering for 15-20 hours; then increasing the pressure of hot pressing sintering to 30-40 MPa, heating to 1900-2000°C, hot pressing sintering for 1-2 hours, and cooling to room temperature;
[0009] 4) placing the product of step 3) in a high-temperature furnace and performing two-stage tempering under the protection of an inert atmosphere to obtain the temperature-resistant ceramic material.
[0010] Furthermore, the SiC fiber has a diameter of 8-10 microns and a length of 100-1000 microns.
[0011] Furthermore, the B 4 The average particle size of C powder is 10-20 microns.
[0012] Furthermore, the ZrO 2 Pink, Y 2 O 3 Pink, Ta 2 O 5 The average particle size of the powder is independently 0.5-2 microns.
[0013] Furthermore, it is characterized in that HfO 2 The average particle size of the powder is 0.1-0.2 microns.
[0014] Furthermore, in step 2), the weight percentages of the components are: 65-75 weight percentages of modified SiC fiber, B 4 C powder 12-15 parts, ZrO 2 8-10 parts of flour, Y 2 O 3 3-3.5 parts of powder, Ta 2 O 5 1-2 parts of powder and HfO 2 0.5-1 part powder.
[0015] Furthermore, the step 1) is to place the SiC fiber in an atmosphere furnace, heat it to 850-950°C under argon protection, introduce oxygen, wherein the volume ratio of the introduced oxygen to argon is 5-10:100, and the introduction and insulation time is 15-30 minutes; and naturally cool it to room temperature under argon protection and take it out to obtain modified SiC fiber.
[0016] Furthermore, in step 4), the specific process of tempering is, under argon protection, heating to 800-900°C and keeping it for 15-30 minutes, then heating to 1100-1200°C and keeping it for 5-10 minutes, performing two-stage tempering, and then cooling to room temperature.
[0017] Furthermore, a temperature-resistant ceramic material is provided, and the temperature-resistant ceramic material is prepared by the method described.
[0018] Beneficial technical effects:
[0019] Compared with the prior art, the beneficial effects of the present invention are:
[0020] 1) By first oxidizing the surface of SiC, dense SiO can be generated on the fiber surface. 2 layer, and this layer is at 1450-1550℃, and the smaller particle size ZrO 2 , Y 2 O 3 Reaction occurs, and some Y ions are embedded into SiO 2 layer, forming a ratio of SiO 2 More stable Y 2 Si 2 O 7 / ZrO 2 Composite materials, Ta 2 O 5 and HfO 2 The powder forms Hf-doped YTaO on the surface of SiC fiber 4 layer, which improves the high temperature toughness and mechanical properties of SiC materials.
[0021] 2) At 1900-2000℃, through short-time high-temperature sintering, SiC fiber material and large-size B 4 C composite to improve the mechanical strength of the product. 2 , Y 2 O 3 With B 4 C reaction to form a higher hardness metal boride ZrB 2 -(YB 6 / YB 4 ).
[0022] 3) The material undergoes a two-stage tempering process at different temperatures to improve its bending resistance and high temperature toughness. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with specific embodiments. However, the protection scope of the present invention is not limited to the following embodiments, and any non-essential adjustments and modifications made to the present invention based on the above invention content still fall within the protection scope of the present invention.
[0024] Example 1
[0025] 1) Place SiC fiber with a diameter of 8 microns and a length of 200 microns in an atmosphere furnace, heat it to 850°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 5:100, and the introduction and insulation time is 30 minutes; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0026] 2) Weigh 65 parts of modified SiC fiber, B 4 C powder 12 parts, ZrO 2 8 parts powder, Y 2 O 3 3 parts powder, Ta 2 O 5 1 part powder and HfO 2 0.5 parts of powder are mixed evenly; wherein the B 4 The average particle size of C powder is 10 microns; ZrO 2 The average particle size of the powder is 0.5 micron, 2 O 3 The average particle size of the powder is 0.5 micron, Ta 2 O 5 The average particle size of the powder is 0.5 micron, HfO 2 The average particle size of the powder is 0.1 micron;
[0027] 3) placing the mixture in a hot pressing sintering furnace at a pressure of 20 MPa, heating to 1450°C under the protection of argon, and hot pressing sintering for 20 hours; then increasing the pressure of hot pressing sintering to 40 MPa, heating to 1900°C, hot pressing sintering for 2 hours, and cooling to room temperature;
[0028] 4) placing the product of step 3) in a high temperature furnace, under the protection of argon, heating to 800°C and keeping it for 30 minutes, then heating to 1100°C and keeping it for 10 minutes, and then cooling to room temperature to obtain a sample.
[0029] Example 2
[0030] 1) Place SiC fiber with a diameter of 10 μm and a length of 200 μm in an atmosphere furnace, heat it to 950°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 10:100, and the introduction and insulation time is 15 min; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0031] 2) Weigh 75 parts of modified SiC fiber, B 4 C powder 15 parts, ZrO 2 10 parts powder, Y 2 O 3 3.5 parts of powder, Ta 2 O 5 2 parts powder and HfO 2 1 part of powder is mixed evenly; wherein B 4 The average particle size of C powder is 20 microns; ZrO 2 The average particle size of the powder is 2 microns, 2 O 3 The average particle size of the powder is 2 microns, Ta 2 O 5 The average particle size of the powder is 2 microns, HfO 2 The average particle size of the powder is 0.2 microns;
[0032] 3) The mixture is placed in a hot pressing sintering furnace at a pressure of 20 MPa. Under the protection of argon, the temperature is raised to 1550°C and hot pressing sintering is performed for 15 hours. Then, the pressure of hot pressing sintering is increased to 40 MPa, the temperature is raised to 2000°C, hot pressing sintering is performed for 1 hour, and then cooled to room temperature.
[0033] 4) placing the product of step 3) in a high temperature furnace, under the protection of argon, heating to 900°C and keeping it for 15 minutes, then heating to 1200°C and keeping it for 5 minutes, and then cooling to room temperature to obtain a sample.
[0034] Example 3
[0035] 1) Place SiC fiber with a diameter of 10 microns and a length of 200 microns in an atmosphere furnace, heat it to 900°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 6:100, and the introduction and insulation time is 20 minutes; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0036] 2) Weigh 70 parts of modified SiC fiber, B 4 C powder 12 parts, ZrO 2 9 parts powder, Y 2 O 3 3.2 parts of powder, Ta 2 O 5 1.4 parts of powder and HfO 20.8 parts of powder were mixed evenly; wherein B 4 The average particle size of C powder is 12 microns; ZrO 2 The average particle size of the powder is 1 micron, 2 O 3 The average particle size of the powder is 1 micron, Ta 2 O 5 The average particle size of the powder is 1 micron, HfO 2 The average particle size of the powder is 0.15 microns;
[0037] 3) The mixture was placed in a hot pressing sintering furnace at a pressure of 20 MPa. Under the protection of argon, the temperature was raised to 1500°C and hot pressing sintering was performed for 16 hours. Then, the pressure of hot pressing sintering was increased to 40 MPa, the temperature was raised to 1950°C, hot pressing sintering was performed for 1.5 hours, and then cooled to room temperature.
[0038] 4) The product of step 3) is placed in a high temperature furnace, and under the protection of argon, the temperature is raised to 850°C and kept for 20 minutes, and then the temperature is raised to 1150°C and kept for 6 minutes, and then cooled to room temperature to obtain a sample.
[0039] Example 4
[0040] 1) SiC fiber with a diameter of 10 μm and a length of 200 μm is placed in an atmosphere furnace, heated to 920°C under argon protection, and oxygen is introduced, wherein the volume ratio of oxygen to argon is 8:100, and the introduction and insulation time is 25 min; the fiber is naturally cooled to room temperature under argon protection and taken out to obtain modified SiC fiber;
[0041] 2) Weigh 72 parts of modified SiC fiber, B 4 C powder 14 parts, ZrO 2 10 parts powder, Y 2 O 3 3 parts powder, Ta 2 O 5 1.8 parts of powder and HfO 2 0.6 parts of powder were mixed evenly; wherein B 4 The average particle size of C powder is 15 microns; ZrO 2 The average particle size of the powder is 1.2 microns, 2 O 3 The average particle size of the powder is 0.8 microns. 2 O 5 The average particle size of the powder is 1.2 microns, HfO 2 The average particle size of the powder is 0.2 microns;
[0042] 3) The mixture was placed in a hot pressing furnace at a pressure of 20 MPa. Under the protection of argon, the temperature was raised to 1520°C and hot pressing was performed for 18 hours. Then, the pressure of hot pressing was increased to 40 MPa, the temperature was raised to 1950°C, hot pressing was performed for 1.2 hours, and then cooled to room temperature.
[0043] 4) The product of step 3) is placed in a high temperature furnace, and under the protection of argon, the temperature is raised to 850°C and kept for 20 minutes, and then the temperature is raised to 1150°C and kept for 6 minutes, and then cooled to room temperature to obtain a sample.
[0044] Example 5
[0045] 1) Place SiC fiber with a diameter of 10 μm and a length of 200 μm in an atmosphere furnace, heat it to 900°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 9:100, and the introduction and insulation time is 25 min; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0046] 2) Weigh 68 parts of modified SiC fiber, B 4 C powder 15 parts, ZrO 2 8 parts powder, Y 2 O 3 3.5 parts of powder, Ta 2 O 5 1.5 parts of powder and HfO 2 0.8 parts of powder were mixed evenly; wherein B 4 The average particle size of C powder is 18 microns; ZrO 2 The average particle size of the powder is 1.5 microns, 2 O 3 The average particle size of the powder is 1.5 microns. 2 O 5 The average particle size of the powder is 2 microns, HfO 2 The average particle size of the powder is 0.1 micron;
[0047] 3) The mixture was placed in a hot pressing sintering furnace at a pressure of 20 MPa. Under the protection of argon, the temperature was raised to 1450°C and hot pressing sintering was performed for 18 hours. Then, the pressure of hot pressing sintering was increased to 40 MPa, the temperature was raised to 1920°C, hot pressing sintering was performed for 1.6 hours, and then cooled to room temperature.
[0048] 4) placing the product of step 3) in a high temperature furnace, under the protection of argon, heating to 860°C and keeping it for 18 minutes, then heating to 1150°C and keeping it for 8 minutes, and then cooling to room temperature to obtain a sample.
[0049] Comparative Example 1
[0050] 1) Weigh 65 parts of SiC fiber with a diameter of 8 microns and a length of 200 microns, B 4 C powder 12 parts, ZrO 2 8 parts powder, Y 2 O 3 3 parts powder, Ta 2 O 5 1 part powder and HfO 2 0.5 parts of powder are mixed evenly; wherein the B 4 The average particle size of C powder is 10 microns; ZrO 2 The average particle size of the powder is 0.5 micron, 2 O 3 The average particle size of the powder is 0.5 micron, Ta 2 O 5 The average particle size of the powder is 0.5 micron, HfO 2 The average particle size of the powder is 0.1 micron;
[0051] 2) placing the mixture in a hot pressing sintering furnace at a pressure of 20 MPa, heating to 1450°C under the protection of argon, and hot pressing sintering for 20 h; then increasing the pressure of hot pressing sintering to 40 MPa, heating to 1900°C, hot pressing sintering for 2 h, and cooling to room temperature;
[0052] 3) The product of step 2) was placed in a high temperature furnace, and under the protection of argon, the temperature was raised to 800°C and kept for 30 minutes, and then the temperature was raised to 1100°C and kept for 10 minutes, and then cooled to room temperature to obtain a comparative sample.
[0053] Comparative Example 2
[0054] 1) Place SiC fiber with a diameter of 8 microns and a length of 200 microns in an atmosphere furnace, heat it to 850°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 5:100, and the introduction and insulation time is 30 minutes; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0055] 2) Weigh 65 parts of modified SiC fiber, B 4 C powder 12 parts, ZrO 2 8 parts powder, Y 2 O 3 3 parts of powder are mixed evenly; wherein B 4 The average particle size of C powder is 10 microns; ZrO 2 The average particle size of the powder is 0.5 micron, 2 O 3 The average particle size of the powder is 0.5 microns;
[0056] 3) placing the mixture in a hot pressing sintering furnace at a pressure of 20 MPa, heating to 1450°C under the protection of argon, and hot pressing sintering for 20 hours; then increasing the pressure of hot pressing sintering to 40 MPa, heating to 1900°C, hot pressing sintering for 2 hours, and cooling to room temperature;
[0057] 4) The product of step 3) was placed in a high temperature furnace, and under the protection of argon, the temperature was raised to 800°C and kept for 30 minutes, and then the temperature was raised to 1100°C and kept for 10 minutes, and then cooled to room temperature to obtain a comparative sample.
[0058] Comparative Example 3
[0059] 1) Place SiC fiber with a diameter of 8 microns and a length of 200 microns in an atmosphere furnace, heat it to 850°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 5:100, and the introduction and insulation time is 30 minutes; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0060] 2) Weigh 65 parts of modified SiC fiber, B 4 C powder 12 parts, Ta 2 O 5 1 part powder and HfO 2 0.5 parts of powder are mixed evenly; wherein the B 4 The average particle size of C powder is 10 microns; Ta 2 O 5 The average particle size of the powder is 0.5 micron, HfO 2 The average particle size of the powder is 0.1 micron;
[0061] 3) placing the mixture in a hot pressing sintering furnace at a pressure of 20 MPa, heating to 1450°C under the protection of argon, and hot pressing sintering for 20 hours; then increasing the pressure of hot pressing sintering to 40 MPa, heating to 1900°C, hot pressing sintering for 2 hours, and cooling to room temperature;
[0062] 4) The product of step 3) was placed in a high temperature furnace, and under the protection of argon, the temperature was raised to 800°C and kept for 30 minutes, and then the temperature was raised to 1100°C and kept for 10 minutes, and then cooled to room temperature to obtain a comparative sample.
[0063] Comparative Example 4
[0064] 1) Place SiC fiber with a diameter of 8 microns and a length of 200 microns in an atmosphere furnace, heat it to 850°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 5:100, and the introduction and insulation time is 30 minutes; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0065] 2) Weigh 65 parts of modified SiC fiber, B 4 C powder 12 parts, ZrO 2 8 portions of powder, Ta 2 O 5 1 part of powder is mixed evenly; wherein B 4 The average particle size of C powder is 10 microns; ZrO 2 The average particle size of the powder is 0.5 micron, Ta 2 O 5 The average particle size of the powder is 0.5 microns;
[0066] 3) placing the mixture in a hot pressing sintering furnace at a pressure of 20 MPa, heating to 1450°C under the protection of argon, and hot pressing sintering for 20 hours; then increasing the pressure of hot pressing sintering to 40 MPa, heating to 1900°C, hot pressing sintering for 2 hours, and cooling to room temperature;
[0067] 4) The product of step 3) was placed in a high temperature furnace, and under the protection of argon, the temperature was raised to 800°C and kept for 30 minutes, and then the temperature was raised to 1100°C and kept for 10 minutes, and then cooled to room temperature to obtain a comparative sample.
[0068] Comparative Example 5
[0069] 1) Place SiC fiber with a diameter of 8 microns and a length of 200 microns in an atmosphere furnace, heat it to 850°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 5:100, and the introduction and insulation time is 30 minutes; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0070] 2) Weigh 65 parts of modified SiC fiber, B 4 C powder 12 parts, Y 2 O 3 3 parts powder, Ta 2 O 5 1 part powder and HfO 2 0.5 parts of powder are mixed evenly; wherein the B 4 The average particle size of C powder is 10 microns; 2 O 3 The average particle size of the powder is 0.5 micron, Ta 2 O 5 The average particle size of the powder is 0.5 micron, HfO 2 The average particle size of the powder is 0.1 micron;
[0071] 3) placing the mixture in a hot pressing sintering furnace at a pressure of 20 MPa, heating to 1450°C under the protection of argon, and hot pressing sintering for 20 hours; then increasing the pressure of hot pressing sintering to 40 MPa, heating to 1900°C, hot pressing sintering for 2 hours, and cooling to room temperature;
[0072] 4) The product of step 3) was placed in a high temperature furnace, and under the protection of argon, the temperature was raised to 800°C and kept for 30 minutes, and then the temperature was raised to 1100°C and kept for 10 minutes, and then cooled to room temperature to obtain a comparative sample.
[0073] Comparative Example 6
[0074] 1) Place SiC fiber with a diameter of 8 microns and a length of 200 microns in an atmosphere furnace, heat it to 850°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 5:100, and the introduction and insulation time is 30 minutes; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0075] 2) Weigh 65 parts of modified SiC fiber, ZrO 2 8 parts powder, Y 2 O 3 3 parts powder, Ta 2 O 5 1 part powder and HfO 2 0.5 parts of powder were mixed evenly; wherein the ZrO 2 The average particle size of the powder is 0.5 micron, 2 O 3 The average particle size of the powder is 0.5 micron, Ta 2 O 5 The average particle size of the powder is 0.5 micron, HfO 2 The average particle size of the powder is 0.1 micron;
[0076] 3) placing the mixture in a hot pressing sintering furnace at a pressure of 20 MPa, heating to 1450°C under the protection of argon, and hot pressing sintering for 20 hours; then increasing the pressure of hot pressing sintering to 40 MPa, heating to 1900°C, hot pressing sintering for 2 hours, and cooling to room temperature;
[0077] 4) The product of step 3) was placed in a high temperature furnace, and under the protection of argon, the temperature was raised to 800°C and kept for 30 minutes, and then the temperature was raised to 1100°C and kept for 10 minutes, and then cooled to room temperature to obtain a comparative sample.
[0078] Comparative Example 7
[0079] 1) Place SiC fiber with a diameter of 8 microns and a length of 200 microns in an atmosphere furnace, heat it to 850°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 5:100, and the introduction and insulation time is 30 minutes; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0080] 2) Weigh 65 parts of modified SiC fiber, B 4C powder 12 parts, ZrO 2 8 parts powder, Y 2 O 3 3 parts powder, Ta 2 O 5 1 part powder and HfO 2 0.5 parts of powder are mixed evenly; wherein the B 4 The average particle size of C powder is 10 microns; ZrO 2 The average particle size of the powder is 0.5 micron, 2 O 3 The average particle size of the powder is 0.5 micron, Ta 2 O 5 The average particle size of the powder is 0.5 micron, HfO 2 The average particle size of the powder is 0.1 micron;
[0081] 3) The mixture was placed in a hot pressing sintering furnace at a pressure of 20 MPa. Under the protection of argon, the temperature was raised to 1450°C, hot pressing and sintering was performed for 25 hours, and then cooled to room temperature.
[0082] 4) The product of step 3) was placed in a high temperature furnace, and under the protection of argon, the temperature was raised to 800°C and kept for 30 minutes, and then the temperature was raised to 1100°C and kept for 10 minutes, and then cooled to room temperature to obtain a comparative sample.
[0083] Comparative Example 8
[0084] 1) Place SiC fiber with a diameter of 8 microns and a length of 200 microns in an atmosphere furnace, heat it to 850°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 5:100, and the introduction and insulation time is 30 minutes; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0085] 2) Weigh 65 parts of modified SiC fiber, B 4 C powder 12 parts, ZrO 2 8 parts powder, Y 2 O 3 3 parts powder, Ta 2 O 5 1 part powder and HfO 2 0.5 parts of powder are mixed evenly; wherein the B 4 The average particle size of C powder is 10 microns; ZrO 2 The average particle size of the powder is 0.5 micron, 2 O 3 The average particle size of the powder is 0.5 micron, Ta 2 O 5 The average particle size of the powder is 0.5 micron, HfO 2 The average particle size of the powder is 0.1 micron;
[0086] 3) placing the mixture in a hot pressing sintering furnace at a pressure of 40 MPa, heating to 1900°C under the protection of argon, hot pressing and sintering for 20 hours, and cooling to room temperature;
[0087] 4) The product of step 3) was placed in a high temperature furnace, and under the protection of argon, the temperature was raised to 800°C and kept for 30 minutes, and then the temperature was raised to 1100°C and kept for 10 minutes, and then cooled to room temperature to obtain a comparative sample.
[0088] Comparative Example 9
[0089] 1) Place SiC fiber with a diameter of 8 microns and a length of 200 microns in an atmosphere furnace, heat it to 850°C under argon protection, introduce oxygen, wherein the volume ratio of oxygen to argon is 5:100, and the introduction and insulation time is 30 minutes; cool it naturally to room temperature under argon protection and take it out to obtain modified SiC fiber;
[0090] 2) Weigh 65 parts of modified SiC fiber, B 4 C powder 12 parts, ZrO 2 8 parts powder, Y 2 O 3 3 parts powder, Ta 2 O 5 1 part powder and HfO 2 0.5 parts of powder are mixed evenly; wherein the B 4 The average particle size of C powder is 10 microns; ZrO 2 The average particle size of the powder is 0.5 micron, 2 O 3 The average particle size of the powder is 0.5 micron, Ta 2 O 5 The average particle size of the powder is 0.5 micron, HfO 2 The average particle size of the powder is 0.1 micron;
[0091] 3) placing the mixture in a hot pressing sintering furnace at a pressure of 20 MPa, heating to 1450°C under the protection of argon, and hot pressing sintering for 20 hours; then increasing the pressure of hot pressing sintering to 40 MPa, heating to 1900°C, hot pressing sintering for 2 hours, and cooling to room temperature;
[0092] 4) The product of step 3) was placed in a high temperature furnace, heated to 1100° C. and kept at this temperature for 20 min under the protection of argon gas, and then cooled to room temperature to obtain a comparative sample.
[0093] Performance Testing
[0094] The performance of the ceramic materials of the embodiments and comparative examples of the present invention were tested, and the test results are shown in the following table, where the corrosion weight loss rate is obtained by placing the samples prepared in the embodiments and comparative examples in a tube furnace and subjecting them to a water-oxygen corrosion treatment at 1200°C for 100 hours. The water vapor: oxygen volume ratio was 1:1, and the oxygen was introduced into the tube furnace at a flow rate of 120 mL / min. After the corrosion was completed, the samples were dried, and the weight difference before and after corrosion was measured, and the result was divided by the original weight of the sample to obtain the corrosion weight loss rate.
[0095] Table 1
[0096]
[0097] Results Data
[0098] The experimental data show that, as shown in Example 1, surface oxidation of SiC has a significant effect on high temperature water resistance and mechanical properties, while as shown in Examples 2-5, ZrO 2 , Y 2 O 3 , 2 O 5 and HfO 2 The effect of powder on the high temperature water oxidation resistance and mechanical properties of SiC materials, and it can be seen from Example 6 that B 4 The addition of C improves the mechanical properties of the product, and through comparative examples 7-8, it can be seen that the sintering temperature affects the product composition and the product performance. At the same time, it can be seen from comparative example 9 that the material improves the mechanical properties through two-stage tempering processes at different temperatures. Referring to Examples 1-5 of the present invention, the materials obtained by the present invention have excellent mechanical properties and high-temperature water and oxygen resistance.
[0099] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.
Claims
1. A method for preparing a temperature-resistant ceramic material, characterized in that: The method comprises: 1) Placing the SiC fiber in an atmosphere furnace and heating it in an oxidizing atmosphere to oxidize the surface of the SiC fiber to obtain modified SiC fiber; 2) Weigh modified SiC fiber, B4C powder, ZrO2 powder, Y2O3 powder, Ta2O5 powder and HfO2 powder and mix them evenly; wherein the average particle size of B4C powder is larger than the diameter of the SiC fiber, and the average particle size of ZrO2 powder, Y2O3 powder and Ta2O5 powder is smaller than the diameter of the SiC fiber; the mass fractions of each component are: 65-75 parts of modified SiC fiber, 12-15 parts of B4C powder, 8-10 parts of ZrO2 powder, 3-3.5 parts of Y2O3 powder, 1-2 parts of Ta2O5 powder and 0.5-1 parts of HfO2 powder; 3) placing the mixture in a hot pressing sintering furnace at a pressure of 20-30 MPa, heating to 1450-1550°C under argon protection, and hot pressing sintering for 15-20 hours; then increasing the pressure of hot pressing sintering to 30-40 MPa, heating to 1900-2000°C, hot pressing sintering for 1-2 hours, and cooling to room temperature; 4) placing the product of step 3) in a high-temperature furnace and performing two-stage tempering under the protection of an inert atmosphere to obtain the temperature-resistant ceramic material.
2. A preparation method according to claim 1, characterized in that: The SiC fiber has a diameter of 8-10 microns and a length of 100-1000 microns.
3. A preparation method according to claim 1, characterized in that: The average particle size of the B4C powder is 10-20 microns.
4. A preparation method according to claim 1, characterized in that: The average particle sizes of the ZrO2 powder, Y2O3 powder and Ta2O5 powder are independently 0.5-2 microns.
5. A preparation method according to claim 1, characterized in that: The average particle size of HfO2 powder is 0.1-0.2 microns.
6. A preparation method according to any one of claims 1 to 5, characterized in that: The step 1) is to place the SiC fiber in an atmosphere furnace, heat it to 850-950° C. under argon protection, introduce oxygen, wherein the volume ratio of the introduced oxygen to argon is 5-10:100, and the introduction and insulation time is 15-30 minutes; and naturally cool it to room temperature under argon protection and take it out to obtain modified SiC fiber.
7. A preparation method according to any one of claims 1 to 5, characterized in that: In step 4), the specific process of tempering is to heat to 800-900°C and keep it for 15-30 minutes under argon protection, then heat to 1100-1200°C and keep it for 5-10 minutes, perform two-stage tempering, and then cool to room temperature.
8. A temperature-resistant ceramic material, characterized in that: The temperature-resistant ceramic material is prepared by the preparation method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Boron carbide ceramic as well as preparation method and application thereof
CN113896552A
Preparation method of antioxidant SiCf / SiC-HfB2 composite material
CN116813363A